Visual motor integration: generation, development, and its importance for ophthalmology - E.A. Egorov; T.B. Romanova; E.G. Rybakova (РМЖ "Клиническая офтальмология")
E.A. Egorov, T.B. Romanova, E.G. Rybakova Pirogov Russian National Research Medical University, Moscow, Russian Federation Visual motor coordination (VMC) is the coordination of the motions and their elements resulting from the collaborative and simultaneous activity of the visual and motor analyzers required for daily activities, sports, and professional activities. The development of VMI begins in the early childhood and proceeds throughout human life being the most active within the first 10 years. VMC is a part of visual motor integration (VMI) defined as a complex combination of skills to correctly execute the movements of arms, legs, and body. The potential causes of impaired VMI are arrested development due to living conditions, organization of teaching, individual developmental or health characteristics; nervous system diseases (i.e., head injuries, cerebrovascular disorders, intoxication etc.); and, in particular, visual impairments. Since the quality of visual functions is an important component of good VMC, its generation and development require adequate vision correction. It was demonstrated that the degree of myopia may affect school performance in the areas requiring VMI. Optical correction of ametropias improves VMC. This should be considered when managing patients (in particular, children) with refractive errors. Keywords: visual motor coordination, visual and motor analyzers, visual functions, optical correction, micro-level orientation, fine motor skills, synchronization. For citation: Egorov E.A., Romanova T.B., Rybakova E.G. Visual motor integration: generation, development, and its importance for ophthalmology. Russian Journal of Clinical Ophthalmology. 2021;21(1):14–17. DOI: 10.32364/2311-7729-2021-21-1-14-17.